Instruments development for measuring student worksheet media based on scientific approaches - Mery Berlian; Dindawini Salsabilla Dinda; Rian Vebrianto (Jurnal Pijar Mipa, 2023)
Student Worksheets a media in the form of sheets containing tasks and activities that students must carry out, which are useful in supporting the learning process, one of which is in the material on the Structure and Function of Plant Tissues so that students can be active in the learning process. An assessment instrument is needed for the Student Worksheets. For this reason, this study aimed to measure the instrument's validity and reliability for using Student Worksheets as a learning media. This study used Research and Development (RND) methodology with an instrument in the form of a Student Worksheets measurement questionnaire consisting of three constructs: product design, material feasibility, and language feasibility. This research was carried out by involving seven teachers from several schools. Data were obtained by distributing the questionnaire via a Google form from September to October 2022 by obtaining prior consent from the respondents. The data obtained were quantitative, then analyzed using SPSS version 29 in the form of Alpha Cronbach analysis. The results of the test show that the validity of the instrument data meets the valid and reliable criteria with each Cronbach Alpha value per construct, namely Product Design (0.795), Material Feasibility (0.712), and Language Feasibility (0.712). Therefore, this study shows that the developed instrument meets the use requirements in developing Student Worksheets media students. Thus, stakeholders and teachers can use this instrument to develop media, particularly Student Worksheets, whereas further researchers can use this instrument to measure media before the study.